Medical illness in gymnasts - Armento, A.; Sweeney, E. (Gymnastics medicine - evaluation, management and rehabilitation, 2020)
Infectious diseases can occur in gymnasts, similar to other athletes. Up to 50% of all high school and college training room visits are due to infectious diseases. Infections can impair the physiological and psychological performance of gymnasts, though there are very few studies that quantify performance deficits in athletes with infections. Poor personal or equipment hygiene, excessive training, and close contact with other athletes can increase the risk of infections in gymnasts. Skin infections may occur by direct contact with another infected athlete or with a mat, or other piece of equipment. Respiratory infections may also occur commonly in gymnasts, especially in poorly ventilated areas. Gastroenteritis-related infections tend to occur in athletes who share water bottles or who have poor hand hygiene. Because infections that occur in gymnasts are not well studied and are very similar to athletes in dance, wrestling, and swimming, some of the concepts in this section are based on studies not specific to gymnasts.